Analisis Akuntanbilitas dan Transparansi Atas Pengelolaan Dana Wakaf di Badan Wakaf Indonesia Perwakilan SUMUT - Nadya Laras Redytha; Mhd Karya Satya Azhar; Ruswan Nurmadi (Universitas Muhammadiyah Enrekang, 2022)
The purpose of this study is to the application of transparency and accountability of Badan Wakaf Indonesia Perwakilan Sumut. This research used descriptive qualitative approach, the data obtained in the interview, and documentation. The results of data analysis showed that most of the principles of transparency as measured by indicators of the handbook accountability aid management humanitarian indonesia stated Badan Wakaf Indonesia Perwakilan Sumuthas applied the principle of transparency by an indicators of the information that is easily understood by wakif, their publication about the activities and financial details provided directly to wakif. Additionally, Badan Wakaf Indonesia Perwakilan Sumut has also applied the principles of accountability as measured by indicators of Wahida (2015), but Badan Wakaf Indonesia board doesn’t have an alternative program. Badan Wakaf Indonesia board only runs programs that have been previously designed.